2020
DOI: 10.1039/d0tb00212g
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-assisted in vivo polymerisation of conjugated oligomer based conductors

Abstract: The conjugated oligomer ETE-S is enzymatically polymerized in vitro, in the presence of peroxidase and H2O2. This polymerization route occurs also in the plant cell wall where ETE-S polymerizes and forms conductors along the plant structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 28 publications
0
56
0
Order By: Relevance
“…The cross-section images, both longitudinal and transversal, showed that the polymer localized only on the epidermis/exodermis cell layers of the root and this was independent of the root developmental stages. Although, as previously demonstrated, internal tissue from plants such as xylem or pith cells have the machinery to polymerize ETE-S, 11,17 ETE-S did neither reached nor polymerized within the internal structure of the intact roots. In some cases, when roots were wounded, we observed polymerization of ETE-S in the internal tissue (Fig.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…The cross-section images, both longitudinal and transversal, showed that the polymer localized only on the epidermis/exodermis cell layers of the root and this was independent of the root developmental stages. Although, as previously demonstrated, internal tissue from plants such as xylem or pith cells have the machinery to polymerize ETE-S, 11,17 ETE-S did neither reached nor polymerized within the internal structure of the intact roots. In some cases, when roots were wounded, we observed polymerization of ETE-S in the internal tissue (Fig.…”
Section: Resultsmentioning
confidence: 58%
“…As previously shown, ETE-S polymerizes enzymatically due to the activity of cell wall peroxidases in the presence of endogenous H 2 O 2 . 17 Initially, the polymerization is slow because it is limited by the diffusion of ETE-S to the root surface and within the cell walls. When the ETE-S molecules react with peroxidases they will oxidize and when two ETE-S radicals combine, dimers will form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-defined pattern in screen-printing is often obtained using high viscosity ink solution, in order to produce thick film (>1 μm), while the resolution is determined from the mesh size and is generally in the range of 100 μm 56 . One of the most peculiar advantages of using organic semiconducting molecules to fabricate electronic circuit and devices is represented by the fact that some of these molecules can actively interact with biological units, polymerising inside the living system itself [58][59][60] . Recently it has been proved that 3-4,ethylenedioxythiophene (EDOT) based trimer can be absorbed by biological system and be polymerised by enzymatic units, physiologically present in the tissue, to create conductive pathways within the biological system 61 FET devices didn't successfully perform until 1957, when the engineer Mohamed Atalla, studying the semiconducting properties of silicon, had the brilliant idea to passivate the surface with a layer of silicon oxide 63 .…”
Section: Fabrication Methodsmentioning
confidence: 99%
“…The negative charge is conferred by a sulfonate residue, linked to a terthio-phene molecule [ 494 ] or to an EDOT-thiophene-EDOT trimer ( Scheme 25 , III). In this case, the sulfonate is connected to the trimer through an ether spacer [ 271 , 495 , 496 , 497 , 498 ].…”
Section: Trimer Structuresmentioning
confidence: 99%